2003
DOI: 10.1080/10575630210028019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultraviolet Light Absorbers on Photostabilization of Azadirachtin-A in Solution (Part: II)

Abstract: The effect of photostabilization of azadirachtin-A (Aza-A) was examined in solutions when exposed to UV radiation, in the presence of four structurally different UV absorbers namely, p-aminobenzoic acid, 2,4-dihydroxybenzophenone, 4,4'-dihydroxybenzophenone and phenyl salicylate. The percentages of Aza-A recovered from the solutions after 6 h exposed to UV radiation in the presence and absence of UV absorbers indicated that the order of stabilization of Aza-A by these absorbers was similar to that obtained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…AZA is a hydrophobic pesticide with low water solubility (0.26 mg mL −1 , 20 °C) . Sunlight or UV can quickly degrade AZA because its molecules contain unstable groups, such as olefinic bond, epoxy, and enol structures . However, traditional formulations of emulsifiable AZA concentrates and dusts employ a large amount of organic reagents, which are not conducive to reducing environmental pollution, promoting food safety and human health.…”
Section: Introductionmentioning
confidence: 99%
“…AZA is a hydrophobic pesticide with low water solubility (0.26 mg mL −1 , 20 °C) . Sunlight or UV can quickly degrade AZA because its molecules contain unstable groups, such as olefinic bond, epoxy, and enol structures . However, traditional formulations of emulsifiable AZA concentrates and dusts employ a large amount of organic reagents, which are not conducive to reducing environmental pollution, promoting food safety and human health.…”
Section: Introductionmentioning
confidence: 99%
“…Photodegradation of pesticides in various phases has been comprehensively studied by several groups. (Maliakal et al 2002; McGarry et al 1997; Klopffer 1977; Franko et al 2005; Katagi 2004; Ishaque et al 2013; Eyheraguibel et al 2010; Trivella and Richard 2014; Nguyen et al 2012b; Nguyen et al 2012a; Cohen et al 2001; El-Nahhal et al 2001; Margulies et al 1987;Deota et al 2002) Earlier we reported that phenyl salicylate provides e cient photoprotection of azadirachtin, a neem-based biopesticide, which nds an important place in integrated pest management (IPM), in thin-lm as well as in solution (Fig.3) (Deota et al 2002;Deota et al 2003). Recently we reported effective photostabilization of chlorpyrifos by dialkoxy benzil derivatives (Fig.4) (Patel et al 2019).…”
mentioning
confidence: 99%